If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 15y + 36 = 0 Reorder the terms: 36 + Y + 15y = 0 Solving 36 + Y + 15y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + Y + -36 + 15y = 0 + -36 Reorder the terms: 36 + -36 + Y + 15y = 0 + -36 Combine like terms: 36 + -36 = 0 0 + Y + 15y = 0 + -36 Y + 15y = 0 + -36 Combine like terms: 0 + -36 = -36 Y + 15y = -36 Add '-15y' to each side of the equation. Y + 15y + -15y = -36 + -15y Combine like terms: 15y + -15y = 0 Y + 0 = -36 + -15y Y = -36 + -15y Simplifying Y = -36 + -15y
| 2x+15=-2x-5 | | -3y-9y=4/5 | | 8x^2-5x-8=0 | | 4(y-9)=-6(5+y) | | 6x-52=3x | | 0.66q+0.75=0.5 | | 4(x+3)=-5 | | 8x+15+3x+20= | | 15+y=2y-7 | | 12/35=6/7n | | 7a+25=60+2a | | -14x=-5x+36 | | s-35=20 | | 30r^3+85r^2-70r= | | 6-(2-4x)+5=3(1-3x) | | 27+4x=7 | | 3x-t=2x | | r+31=-3(1-6r) | | -2(-2x+3)=-10x-8 | | 4x-1=-2x+7 | | 6x+4(-3x-4)=44 | | -2(8-5x)=-126 | | 3x^4+2x-4=0 | | x^2-24x=-35 | | N-/6=20 | | 1.2/y=2.4/3.4 | | 2x^4+2x-4=0 | | 9-7x=-3x-15 | | Z^2-18z=66 | | =2x^2+x-7 | | 24x^4+23x^3+60x^2-125x-500=0 | | (2x)+142=180 |